Synthesis, radiolabelling and pharmacological evaluation of CO-releasing molecules - Giffard, Dylan (Department of Chemistry, 2019)
The combatting of drug-resistant cancerous cell lines and strains of P. falciparum remain major global health problems to date, with hundreds of thousands of related deaths per annum. Early identification of solid tumours and infections, as well as the discovery of drugs with new mechanisms of action, are paramount in the fight against drug resistance. This study investigates the synthesis, characterisation and biological evaluation of new Mn(I) and Re(I) tricarbonyl metallodendrimers, in addition to the formation of a new 99mTc complex for use in diagnostic imaging. Two series of mono- and multimeric picolylamine ligands based on polyamine scaffolds were prepared. One series of ligands was functionalised with Re(I)- and Mn(I)-tricarbonyl moieties following the [2 + 1] approach, to form a series of cationic complexes. In addition, a second series of neutral bidentate (N,N) Mn(I) complexes were prepared. The ligands and complexes were characterised using a range of spectroscopic and analytical techniques, including 1H, 13C{1H}, and 31P{1H} NMR spectroscopy, infrared spectroscopy, and mass spectrometry. The stability and CO-release properties of the Mn(I) complexes were investigated using UV/Vis absorption spectroscopy. A decrease in the MLCT absorption band suggests the release of CO. CO-release was confirmed using a monomeric Mn(I) complex as a model using the myoglobin assay. The in vitro antiproliferative activity of the Re(I) complexes was investigated against three cancerous cell lines (A431, DLD-1 and A2780) and one non-tumourigenic cell line (BJ). The complexes displayed moderate to good activity, with all IC50 values in the low micromolar range. The tetranuclear complex displayed the highest efficacy against the tested cell lines (IC50 = 6 – 14 µM). Selectivity towards the cancerous cell lines was observed for the tri- and tetranuclear complexes, with higher IC50 values against the BJ cell line. The in vitro antiproliferative activity of the Mn(I) complexes was evaluated against two cancerous cell lines (A431 and A375). The tetranuclear [2 + 1] Mn(I) complex displayed the best activity against both of the tested cell lines. The [2 + 1] complexes displayed higher in vitro activity than their bidentate counterparts. The complexes were evaluated as in vitro antiplasmodial agents against chloroquine-sensitive (NF54) and chloroquine-resistant (K1) strains of P. falciparum. The [2 + 1] Mn(I) complexes displayed enhanced activity over their Re(I) analogues and their bidentate counterparts. The tetranuclear [2 + 1] Mn(I) complex displayed the best activity against the K1 strain (IC50 = 0.99 µM) and the best resistance index (RI = 0.263) of all the tested complexes. Irradiation of selected Mn(I) complexes during incubation with the K1 strain resulted in an almost two-fold increase in activity of the [2 + 1] Mn(I) complexes, but a decrease in activity of the bidentate Mn(I) complexes. Formation of the monomeric radiolabelled product was achieved by reacting 99mTc(bpy)(CO)3 with a monomeric ligand. The product was isolated using preparative HPLC, but the retention time did not match that of the Re(I) analogue, likely due to the difference in counterion. Radiolabelling of the multimeric ligands was unsuccessful.